Environmental Income and Rural Livelihoods: A Global-Comparative Analysis - Angelsen, A.; Jagger, P.; Babigumira, R.; Belcher, B.; Hogarth, N.J; Bauch, S.; Börner, J.; Smith-Hall, C.; Wunder, Sven (Elsevier, 2014)
This paper presents results from a comparative analysis of environmental income from approximately 8000 households in 24 developing countries collected by research partners in CIFOR’s Poverty Environment Network (PEN). Environmental income accounts for 28% of total household income, 77% of which comes from natural forests. Environmental income shares are higher for low-income households, but differences across income quintiles are less pronounced than previously thought. The poor rely more heavily on subsistence products such as wood fuels and wild foods, and on products harvested from natural areas other than forests. In absolute terms environmental income is approximately five times higher in the highest income quintile, compared to the two lowest quintiles.